1991
DOI: 10.1080/03079459108418805
|View full text |Cite
|
Sign up to set email alerts
|

Detection of viral antigen following exposure of one‐day‐old chickens to the Holland 52 strain of infectious bronchitis virus

Abstract: SUMMARYOne-day-old specific-pathogen-free single comb White Leghorn chickens were inoculated by eyedrop with either 0.1 ml of phosphate buffered saline containing 10 4.3 EID 50 of the Holland 52 strain of infectious bronchitis virus or normal allantoic fluid. Trachea, caecal tonsils and kidneys were removed from randomly selected birds at 0, 3, 5, 7 and 10 days post-inoculation (pi) and the presence or absence of viral antigen was detected utilizing virus isolation (VI), an indirect fluorescent antibody techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 17 publications
3
43
1
2
Order By: Relevance
“…The performance of the IPA in detecting IBV antigen after inoculation of SPF chickens compares very favourably with IFA (Nakamura et al, 1991;Owen et al, 1991;Janse et al, 1994;Chen et al, 1996). Naqi (1990) showed that IBV could be detected by IPA in the CAM of inoculated eggs within 15 h p.i., with a detection limit of 10 6.2 EID 50 .…”
Section: Detection Of Ibv Antigenmentioning
confidence: 88%
See 2 more Smart Citations
“…The performance of the IPA in detecting IBV antigen after inoculation of SPF chickens compares very favourably with IFA (Nakamura et al, 1991;Owen et al, 1991;Janse et al, 1994;Chen et al, 1996). Naqi (1990) showed that IBV could be detected by IPA in the CAM of inoculated eggs within 15 h p.i., with a detection limit of 10 6.2 EID 50 .…”
Section: Detection Of Ibv Antigenmentioning
confidence: 88%
“…Many papers have been published on the duration of IBV infections in the chicken (Hofstad & Yoder, 1966;Doherty, 1967;Colwell & Lukert, 1969;Cook, 1971;Crinion et al, 1971;Jones & Jordan, 1972;Hawkes et al, 1983;Smith et al, 1985;ElHouadfi et al, 1986;Jones & Ambali, 1987;Bumstead et al, 1989;Ambali & Jones, 1990;Otsuki et al, 1990;Nakamura et al, 1991;Owen et al, 1991;Bhattacharjee et al, 1995;Dhinakar Raj & Jones, 1997a;De Wit et al, 1998b). These studies involve a large variety of sampled organs, different virus strains, different doses, etc., and can therefore be expected to present partly conflicting data about the intervals in which the virus can be detected in the various organs.…”
Section: Time Between Start Of Infection and Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…La técnica se realizó de acuerdo a Owen et al (17) Protocolo para el aislamiento de IBV en huevos embrionados SPF (libres de patógenos específicos). Brevemente, los sobrenadantes de las muestras de IBV-positivas (determinada por la detección de virus) se filtraron a través de 0.45 μm; 0.1 ml se inoculó en huevos de gallina embrionados libres de patógenos específicos de 9 días de edad (ICA, Bogotá, Colombia) por la vía cavidad alantoidea.…”
Section: Dna Sequencing and Phylogenetic Analysisunclassified
“…Disadvantages of IFA (compared to virus isolation) are its usually lower sensitivity (Wizigmann et al, 1981;Hilbink et al, 1982;Owen et al, 1991), the occurrence of non-specific reactions (Braune et al, 1965;Yagyu et al, 1990) and the lack of serotype specificity (Lukert, 1969;Lucio & Hitchner, 1970;Yagyu et al, 1990). These disadvantages are more pronounced in field samples than in samples from experimentally infected birds held in isolated conditions.…”
Section: Introductionmentioning
confidence: 98%